The wide window - Snicket, Lemony; Helquist, Brett (London : Egmont, 2001)
Catastrophes and misfortune continue to plague the quick-witted, kind-hearted Baudelaire orphans after they're sent to live with fearful Aunt Josephine who offers little protection against the evil Count Olaf.
Includes book.
Keywords: Humorous fiction; Orphans -- Fiction